Performance of quantitative measurements in [18F]fluorocholine positron emission tomography/computed tomography for parathyroid imaging (P2TH study) - Jacquet-Francillon, Nicolas; Morelec, Isabelle; Germain, Natacha; Prades, Jean-Michel; Habouzit, Vincent; Mariat, Christophe; Bonnefoy, Pierre-Benoit; Prevot, Nathalie (Frontiers in Medicine, 2022)
Objective: [18F]fluorocholine PET/CT is used more and more in addition to [99mTc]Tc-Sestamibi scintigraphy and ultrasonography for the location of hyperfunctioning parathyroid glands. The aim of this study is to evaluate the performance of quantitative criteria in [18F]fluorocholine PET/CT for localization of hyperfunctioning parathyroid glands. The secondary objective is to highlight a correlation between the detection rate of [18F]fluorocholine PET/CT and serum PTH level. Methods: In two academic centers, we retrospectively included patients with biological hyperparathyroidism and who had [18F]fluorocholine PET/CT. After a visual analysis, to measure the overall performance of the [18F]fluorocholine PET/CT, a blind reading was carried out with standardized measurements of SUVmax, Liver Ratio, Thyroid Ratio and Size Ratio. We analyzed quantitative criteria compared to the histological results, in particular to identify differences between adenomas and hyperplasias. We compared the performance of each quantitative criterion to the overall sensitivity, specificity, PPV, NPV and accuracy of the [18F]fluorocholine PET/CT. The detection rate of hyperfunctioning parathyroid glands was calculated in subgroups of serum PTH level. Results: Quantitative criteria in [18F]fluorocholine PET/CT were measured for 120 patients (135 lesions). The areas under the ROC curve representing the SUVmax and the Liver Ratio were significantly increased. The optimal cut-off values represented by the maximum Youden index was for SUVmax >4.12 and for Liver Ratio >27.4. Beyond certain threshold values of SUVmax (>4.12) or Liver Ratio (>38.10), all lesions were adenomas histologically proven. SUVmax and Liver Ratio were significantly higher for adenomas than for hyperplasias and differential diagnosis (p=0.0085 and p=0.0002). The positivity of the [18F]fluorocholine PET/CT was correlated with the PTH level. Detection rates were 55.56%, 75.56% and 87.50% respectively for PTH <70ng/mL, 70 to 120ng/mL, and >120ng/mL. Conclusions: Semi-quantitative measurements (SUVmax and the Liver Ratio) should be considered as additional tools in the interpretation of a [18F]fluorocholine PET/CT. These quantitative parameters have a lower overall performance but a higher specificity than an overall visual analysis to identify an adenoma. Above certain threshold values, all lesions are adenomas. [18F]fluorocholine PET/CT confirms excellent performance for the detection of hyperfunctioning parathyroid. For serum PTH level <70 ng/mL, detection rate of [18F]fluorocholine PET/CT strongly decreased.